Mama Goat, Papa Goat - Mahendren, Mathura (Global Health: Annual Review, 2016)
A story from my time spent working with an NGO focused on health promotion and education in The Gambia. In particular, it recounts an innovative activity used to engaged trainees in a HIV/AIDS and Life Skills training, and highlights the importance of focusing not only on what we teach, but how we teach it.